PEMANFAATAN KITOSAN SEBAGAI ADSORBEN UNTUK MENURUNKAN KADAR LOGAM TEMBAGA (Cu), BESI (Fe), DAN TIMBAL (Pb) - Lestari, Devi Widya; Rodiah, Siti; Asnari, Muhammad (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2024)
Industrial waste in the field of crossing has liquid waste which is processed in Primary Effluent Treatment- Secondary Effluent Treatment (PET-SET) the waste consists of three samples namely Inlet, Aeration, and Outlet which contain heavy metals which result in pollution to the environment, it needs to be overcome through an adsorption method that is easily accessible and economical in use using shrimp skin chitosan adsorbent. Based on the purpose of this case study to determine the capacity of chitosan in adsorbing Cu, Fe, and Pb metals with a chitosan mass ratio of 1-5 g, the optimum condition results were obtained, namely the use of 5 g chitosan on each metal, namely 98%, 95%, 93% for Cu, Fe, and Pb metals. This is due to the influence of the mass of chitosan used, because the more mass of chitosan used, the more the amount of metal that can be absorbed.